MATEC Web of Conferences - Maslov specialist in the field of power engineering Associate Professor of Tomsk Polytechnic University, Candidate of physical and mathematical sciences; Zharova; Faraponov; Kozlov; Matskevich (EDP Sciences, 2018)
The technique and results of the experimental-theoretical study of gas dynamics, heat transfer and the structure of gas flow in the flowing channel of a model hypersonic air-ramjet engine are presented for Mach numbers M (5; 6).